The identity of the Finnish Osmoderma (Coleoptera: Scarabaeidae, Cetoniinae) population established by COI sequencing - Landvik M; Wahlberg N; Roslin T (ENTOMOLOGICA FENNICA, 2022)
The hermit beetle Osmoderma eremita (Coleoptera: Scarabaeidae) is a flagship species for invertebrate conservation efforts by the European Union. This taxon has recently been revealed as a species complex likely encompassing five cryptic species. The northernmost population of Osmoderma is found on the island of Ruissalo in Turku, Finland. This population has been protected as species 0. eremita, but its true species affinity has never been established. To resolve its identity, we sequenced the mitochondrial COI gene from seven specimens sampled in Ruissalo. Based on a phylogenetic hypothesis generated from the sequences combined with previously published data, the Finnish hermit beetle was identified as Osmoderma barnabita. Information regarding the ecology and life cycle of 0. eremita should then not uncritically be assumed to apply to the Finnish population. Rather, the Finnish population should be treated as a separate entity in conservation and management of European Osmoderma.